4 - Of Remedies and Poisons: Recreational Use of Antiretroviral Drugs in the Social Imagination of South African Carers - Fiona Larkan,; Brian Van Wyk,; Jamie Saris, (African Sociological Review, 2010)
During an ethnographic study of barriers to, and compliance with, antiretroviral (ARv) treat- ment in the South Africa’s West Coast region, our team came across a general sense amongst heath careproviders that there was a lively illicit trade in antiretroviral medications. in itself, this is seen to be a barrier to adherence for many of their patients whose medication is traded to, or stolen by, drug dealers. independent anecdotal evidence is emerging about this trade, though there has been little hard data verifying the existence of a recreational market for ARvs. While there are rumours that efavirenz (some of whose side effects are hallucinogenic) is being used in the manufacture of crystal methamphetamine (locally ‘tik’), such reports, in themselves, do not seem able to explain the ubiquity (and the confidence) of the belief in this trade amongst the health care providers with whom we have interacted. This paper explores aspects of the off-label trade of ARvs (as we have come to know it) and, as importantly, how rumor and knowledge of this trade has gained increasing currency in the social imagination of health and social care workers. This, we argue, could precipitate a real crisis in the Government’s public rollout programme.